Degradation of atrazine, glyphosate, and 2,4-D in soils collected from two contrasting crop rotations in Southwest Chaco, Argentina - Luzzi, Johana Inés; Aparicio, Virginia Carolina; De Geronimo, Eduardo; Ledda, Alejandra Rosa; Sauer, Mariana Veronica; Costa, Jose Luis (Taylor & Francis, 2024)
Argentina stands as one of the leading consumers of herbicides. In a laboratory incubation experiment, the persistence and production of degradation metabolites of Atrazine, 2,4-D, and Glyphosate were investigated in a loamy clay soil under two contrasting agricultural practices: continuous soybean cultivation (T1) and intensified rotations with grasses and legumes (T2). The soils were collected from a long-term no-till trial replicating the influence of the meteorological conditions in the productive region. The soil was enriched with diluted concentrations of 6.71, 9.95, and 24 mg a.i./kg-1 of soil for the respective herbicides, equivalent to annual doses commonly used in the productive region. Samples were taken at intervals of 0, 0.5, 1, 2, 4, 6, 8, 16, 32, and 64 days, and analysis was conducted using high-resolution liquid chromatography UPLC MS/MS. An optimal fit to the first-order kinetic model was observed for each herbicide in both rotations, resulting in relatively short half-lives. Intensified crop sequences favored the production of biotic degradation metabolites. The impact of the high frequency of soybean cultivation revealed a trend of soil acidification and a reduced biological contribution to attenuation processes in soil contamination.